The impact of international financial reporting standard (ifrs) adoption on value relevance of accounting information: evidence from Malaysia - Rashid, Rabar Omer (2021)
Value relevance as a field of accounting in developed and developing countries is gaining attention from many scholars especially in the last two decades. In line with the implementation of the International Financial Reporting Standards (IFRSs), several studies were conducted to investigate the real impact of IFRS on the value relevance of accounting information since mixed findings have been reported. In 2006, Malaysia, like most countries began to gradually introduce levels of IFRS to obtain better quality annual reporting and to facilitate investors’ decisions which subsequently became mandatory in 2012. Accordingly, the purpose of this study are (i) to examine the value relevance of accounting information; (ii) to investigate the impact of the mandatory adoption of International Financial Reporting Standards (IFRS) on the value relevance of accounting information among non-financial listed companies in Malaysia, which has not been well researched. This study relied on secondary data from 2007-2016 to cover the periods before and after the adoption of IFRS. This study used a price model for a sample of 4,186 firm-year observations on Bursa Malaysia. The regression analysis concluded that the value of accounting data is relevant among Malaysian companies. Furthermore, this study reported a statistically significant increase in value relevance after the IFRS adoption with regard to the book value of equity and earnings. Nonetheless, investors, regulators and governments will stand to benefit from such a research on the effects of IFRS on financial reporting in Malaysia.